2021
DOI: 10.1021/acsami.1c14944
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Mucoadhesive Hydrogel Induces Chemoresistant Bladder Cancer Ferroptosis through Delivering Iron Oxide Nanoparticles in a Three-Tier Strategy

Abstract: Bladder cancer (BCa) is the most costly solid tumor owing to its high recurrence. Relapsed cancer is known to acquire chemoresistant features after standard intravesical chemotherapy. This cancer state is vulnerable to ferroptosis, which occurs when lipid peroxides generated by iron metabolism accumulate to lethal levels. Increasing the labile iron pool (LIP) by iron oxide nanoparticles (IONPs) promises to inhibit chemoresistant BCa (CRBCa), but systemically administered IONPs do not sufficiently accumulate at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The reason for using hydrogels is that IONPs cannot sufficiently accumulate at tumor site and in addition, increasing iron levels in IONPs promotes their efficacy in chemosensitivity via inducing ferroptosis. The IONPs were modified with HA and they were selectively internalized in bladder tumor cells overexpressing CD44 receptor via endocytosis 195 . As a proof for the statement that both functional and nonfunctional nanomaterials can use endocytosis for internalization in bladder tumor cells, a study reported methotrexate‐loaded magnetic nanostructures are probably internalized via receptor‐mediated endocytosis 196 .…”
Section: Cancer Cell Internalizationmentioning
confidence: 96%
See 1 more Smart Citation
“…The reason for using hydrogels is that IONPs cannot sufficiently accumulate at tumor site and in addition, increasing iron levels in IONPs promotes their efficacy in chemosensitivity via inducing ferroptosis. The IONPs were modified with HA and they were selectively internalized in bladder tumor cells overexpressing CD44 receptor via endocytosis 195 . As a proof for the statement that both functional and nonfunctional nanomaterials can use endocytosis for internalization in bladder tumor cells, a study reported methotrexate‐loaded magnetic nanostructures are probably internalized via receptor‐mediated endocytosis 196 .…”
Section: Cancer Cell Internalizationmentioning
confidence: 96%
“…The IONPs were modified with HA and they were selectively internalized in bladder tumor cells overexpressing CD44 receptor via endocytosis. 195 As a proof for the statement that both functional and nonfunctional nanomaterials can use endocytosis for internalization in bladder tumor cells, a study reported methotrexate‐loaded magnetic nanostructures are probably internalized via receptor‐mediated endocytosis. 196 Although studies have shown the potential of nanoparticles for internalizing into bladder tumor cells via endocytosis, 197 there are major gaps and limitations that should be addressed in future studies.…”
Section: Cancer Cell Internalizationmentioning
confidence: 99%
“…They have several advantages, including a good chemical stability, excellent biocompatibility, passive targeting ability, large specific surface area, good thermal stability, high drug loading, and so on. [130] PLZ4@SeD [84] DOX-PS [85] SeDs [87] Thiolated MSN NPs [131] PAMAM-modified MSNPs [132] FA-TMLs@MNPs-GNRs-DOX [135] LP-gel [148] PLL-P(LP-co-LC) [149] Ur-PDA NC [154] NG/HCPT [155] OEGMA-PTX@Ce6 [156] SS CB GB [157] PEG-PAMAM NPs [160] IONP-HA@Gel [168] KP372-1 [86] Cy3-labeled 293T-R-Fe@OA [174] RT HSA-MnO 2 -CQ [92] CDT AgNPs [125] CONPs [133] nZnO [134] IT IR775@Met@Lip [96] MPDIα W [97] 522NP [98] AB680@EMVs-aPDL1 [99] PGFCS [100] CWS-NP [145] CWS-Nano-CL [146] CWS-FPL [147] Fe 3 O 4 @Chl/Fe CNPs [137] GT siRNA@CS-HAD [102] UMND [103] HNTs/siRNA [104] CRISPR-Cas13a/liposome systems [105] siNrf GCD [164] KDM6A-mRNA NPs [106] SCNTs/si-circPRMT5 [143] PTT Fe 3 O 4 @PDA-VCA-FA SPs [67] HAPO-1048 [112] BBTD+GA/PEG-RGD [113] Cu 2-X Se [128] HA-IR780 NP…”
Section: Nonmetallic Oxide Nanomaterialsmentioning
confidence: 99%
“…Thanks to INOP labeling with hyaluronic acid, the uptake and binding of CD44 occurs, leading to an increase of the labile iron pool that results in ferroptosis of chemoresistant bladder cancer cells. The study conducted on a mouse model has shown that the developed platform providing local sustained high concentrations of IONP‐HA allows a reduction in tumor volume by about 40% compared to the control group 85 . A recent achievement of Afif Shafiq's team is the development of a second‐generation drug delivery system based on a hydrogel combination of Pluronic F127 and methacrylic acid for the controlled release of tolterodine tartrate.…”
Section: Applications Of Hydrogel Materials In the Treatment Of Urina...mentioning
confidence: 99%
“…The team of Zhongming Huang et al 84 Thermosensitive copolymer hydrogel of 3-caprolactone, The team of Ao Qi et al 85 Mucoadhesive hydrogel platform coated with hyaluronic acid (IONP-HA@Gel)…”
Section: Semisynthetic Glycosaminoglycan Ethersmentioning
confidence: 99%